2007
DOI: 10.1016/j.smrv.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous positive airway pressure treatment for sleep apnea in older adults

Abstract: Daytime sleepiness and sleep disordered breathing are increased in older compared to middle-aged adults. The cognitive and cardiovascular sequelae associated with obstructive sleep apnea (OSA) have significant implications for the older adult who may already be suffering from chronic illness. Most of the evidence supporting the utilization of continuous positive airway pressure (CPAP) for the treatment of OSA has been generated from studies employing samples consisting predominately of middle-aged adults. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 54 publications
6
72
1
9
Order By: Relevance
“…In the present study around 70% of the patients tolerated CPAP for at least 4 h per night on average, which, despite some controversy in the literature in this respect, is similar to the percentages found in studies that include elderly patients [33,34]. In this sense, the present study showed a positive correlation between the hours of CPAP use and the improvement in some QSQ domains related to diurnal symptoms, nocturnal symptoms and the emotional sphere.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study around 70% of the patients tolerated CPAP for at least 4 h per night on average, which, despite some controversy in the literature in this respect, is similar to the percentages found in studies that include elderly patients [33,34]. In this sense, the present study showed a positive correlation between the hours of CPAP use and the improvement in some QSQ domains related to diurnal symptoms, nocturnal symptoms and the emotional sphere.…”
Section: Discussionsupporting
confidence: 87%
“…72 Therefore, the STSATF recommended that acceptable criteria for evaluating efficacy of prescribed OSA treatments address these three elements. Specific measures in each domain include a combination of physician judgement, symptom surveys (which may be useful if positive), objective testing, and adherence data.…”
Section: Treatment For Osa: Goals and Assessments Of Efficacymentioning
confidence: 99%
“…9 Elderly patients who use CPAP for OSA have increased alertness; improved neurobehavioral outcomes in cognitive processing, memory, and executive function; and decreased sleep disruption. 10 However, many elderly patients have difficulty accepting and tolerating CPAP, and frequently cease CPAP use. 11,12 CPAP cessation is also a problem in younger patients with OSA; indeed, there does not appear to be any marked difference in the rate of CPAP adherence in different age groups.…”
Section: Introductionmentioning
confidence: 99%